Correlation between belief in science and belief in pseudoscience in high school students - Maghfiroh, Adinda Zahwatun; Pantiwati, Yuni; Husamah, H.; Permana, Tutut Indria; Fauzi, Ahmad (Biosfer: Jurnal Pendidikan Biologi, 2024)
Dissemination of news through social media is one of the biggest causes of increasing student’s trust in pseudoscience. The purpose of this correlational study was to analyze the relationship between belief in science and pseudoscience beliefs related to biology in high school students. This research entails a correlational study conducted through a survey methodology. The results of the study show that the ability to believe in science has a significant effect on students' belief in pseudoscience related to biology for high school students. Based on the research, the initial hypothesis of the study was rejected, that there is a positive relationship between belief in science and belief in pseudoscience related to biology, thus indicating that increasing students' confidence in science will also increase students' confidence in pseudoscience related to biology. This is due to the continuous spread of unscientific issues through social media which will affect the increase in trust in pseudoscience. The increase in pseudoscience is due to the lack of student media literacy so that it can affect the way students respond to news that is on social media. The lack of education regarding students' media literacy is a factor in increasing students' confidence in pseudoscience related to biology for high school students.